2011
DOI: 10.1039/c0pp90035d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solar ultraviolet radiation on terrestrial ecosystems. Patterns, mechanisms, and interactions with climate change

Abstract: Ultraviolet radiation (UV) is a minor fraction of the solar spectrum reaching the ground surface. In this assessment we summarize the results of previous work on the effects of the UV-B component (280-315 nm) on terrestrial ecosystems, and draw attention to important knowledge gaps in our understanding of the interactive effects of UV radiation and climate change. We highlight the following points: (i) The effects of UV-B on the growth of terrestrial plants are relatively small and, because the Montreal Protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
272
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(284 citation statements)
references
References 164 publications
6
272
0
6
Order By: Relevance
“…However, because the recovery is slow and local UV conditions are expected to be modulated by various ozone modifying tropospheric conditions (for example clouds) and climate factors [49], research on plant acclimation strategies to supplemental UV-B is and will remain timely.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the recovery is slow and local UV conditions are expected to be modulated by various ozone modifying tropospheric conditions (for example clouds) and climate factors [49], research on plant acclimation strategies to supplemental UV-B is and will remain timely.…”
Section: Discussionmentioning
confidence: 99%
“…The successful implementation of the Montreal protocol decelerated the weakening of the ozone layer (Egorova et al, 2013;Mäder et al, 2010;Newman and McKenzie, 2011) and many recent studies indicate the first signs of recovery over the Northern Hemisphere (Kuttippurath et al, 2013;McLinden and Fioletov, 2011;Newchurch et al, 2003;Smedley et al, 2012). Signs from the onset of ozone recovery since the late 1990s on surface UV-B irradiance have been mainly detected over the northern high latitudes; recent studies indicate that UV-B has been declining during the last 2 decades (Bernhard, 2011;Eleftheratos et al, 2014). However, during the same period, both the UV-B and the UV-A irradiance are increasing over many locations in the Northern Hemisphere mid-latitudes, mainly due to the negative trends in the amount of clouds and aerosols (De Bock et al, 2014;Fitzka et al, 2012;Román et al, 2015;Smedley et al, 2012;Zerefos et al, 2012).…”
Section: Fountoulakis Et Al: Short-and Long-term Variability Of Smentioning
confidence: 99%
“…In addition, for historical reasons related to studies of the effects of stratospheric ozone depletion (29,30), there has been a strong emphasis on evaluating the effects of UV (200-400 nm) radiation (particularly UV-B, 280-315 nm) on litter decomposition, and these studies have yielded equivocal results with respect to the importance of this spectral region as a driver of photodegradation (31,32). Recent evidence has demonstrated that the visible component of sunlight [blue and green wavelengths, 400-550 nm (BG)] can have a large impact on photodegradation (17,20), suggesting…”
Section: Uv Radiationmentioning
confidence: 99%